Penentuan Cadangan Premi dengan Metode New Jersey pada Asuransi Jiwa Dwiguna Berjangka - Oktaviani, Risqi; Alwi, Wahidah; Sauddin, Adnan (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2019)
in this article discusses about the prospective premium reserve modified using New Jersey method on endowment insurance. The purpose of this article to know how much premium reserve on life insurance company with using New Jersey method. The result premium reserve the end of fifth year  using on life insurance company for the insured at the age 25,30,35,40, and 45 years sequentially is Rp.5.376.856,82, Rp5.388.103,39, Rp5.410.332,27, Rp5.449.476,43, and Rp5.511.600,89 with conmpensation by Rp.10.000.000.